Избранные труды: [в 2 ч.] (Максим Максимович Ковалевский ; сост., авт. вступ. ст. и коммент.: Н. Б. Хайлова ; Ин-т обществ. мысли) - Ковалевский Максим Максимович (2010)
Экземпляры: КХ (20110329) / Инвентарный номер: 1083176 / Цена: / Сис.шифр: 87.3(2) / Авт.знак: К 56 / ГРНТИ: 02 / ББК: 66.1(2)5